Modeling and simulation of genetic algorithm using meta-models - Abbas MAhmoodi Markid (Journal of Hyperstructures, 2018)
In this paper we introduce new method for modeling and simulation of genetic algorithm based on meta-models. Eclipse Modeling Framework (EMF) provides a meta-modeling framework to describe models in various abstraction levels. We use this platform and EMF-DEVS to modeling genetic algorithm (GA-DEVS) and generating partial executable codes on DEVS-Suite simulator. Also this process helps modelers to validate models and their structure and I/O validity.